Design, Formulation and Characterization of Solid-lipid Nanoparticles for Anti-retroviral Drug - Anita H. Pagar (Asian Journal of Pharmaceutics (AJP), 2025)
Treating human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome effectively remains a significant challenge due to issues, such as low absorption, frequent dosing, and side effects associated with traditional antiretroviral drugs. This study focuses at solid lipid nanoparticles (SLNs) as a new way to deliver drugs. These nanoparticles could provide better control over how these drugs are absorbed and released in the body, making treatment more manageable for patients. Materials and Methods: We made SLNs utilizing ultrasonication and high-shear homogenization. A commonly used antiretroviral drug was embedded in a lipid matrix made from glyceryl monostearate and stabilized with Poloxamer 188. Researchers carefully evaluated these nanoparticles for key properties, such as the size of the particles, the size distribution polydispersity index (PDI), and the surface charge (zeta potential), drug retention (entrapment efficiency), and the timing of drug release in lab tests. Results: The resulting SLNs had an average particle size of <200 nanometers and a PDI of <0.3, which means that the size distribution was even. The zeta potential readings showed that the formulation was stable and that drug retention was high, at more than 80%. The in vitro release investigation indicated that the drug was released slowly over a whole 24-h period, which suggests that it could have long-lasting effects. Conclusion: These results show that SLNs could make antiretroviral medications work better in the body. They offer more stable and sustained release and may reduce how often patients need to take their medication. By simplifying dosing and enhancing drug performance, SLNs could play a key role in making HIV treatment more effective and patient-friendly